2017
DOI: 10.1038/s41598-017-05451-5
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Usp9x disrupts cell adhesion, and components of the Wnt and Notch signaling pathways in neural progenitors

Abstract: Development of neural progenitors depends upon the coordination of appropriate intrinsic responses to extrinsic signalling pathways. Here we show the deubiquitylating enzyme, Usp9x regulates components of both intrinsic and extrinsic fate determinants. Nestin-cre mediated ablation of Usp9x from embryonic neural progenitors in vivo resulted in a transient disruption of cell adhesion and apical-basal polarity and, an increased number and ectopic localisation of intermediate neural progenitors. In contrast to oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 72 publications
0
21
0
Order By: Relevance
“…As the first round of genetic testing showed only few colorectal adenocarcinoma-related mutations in goblet cell carcinoids and their ex-goblet cell carcinoid variants, we decided to take our sequencing approach one step further and investigated selected cases from both subgroups with a large-scale next-generation sequencing panel, which covers nearly all exons from 409 cancer-related genes. Interestingly, both goblet cell carcinoids and adenocarcinomas ex-goblet cell carcinoid harbored alterations in genes (USP9X, NOTCH1, CTNNA1, and CTNNB1, TRRAP, respectively), whose transcriptional products are known to be directly involved or interact with the Wnt-signaling pathway, [27][28][29][30][31][32] that is thought to have an important role in intestinal proliferation and differentiation. 35,36 It is therefore possible, that alterations of Wnt-signaling pathwayassociated proteins, beside APC, may be of significance for the development of appendiceal goblet cell carcinoids and their high-grade variants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As the first round of genetic testing showed only few colorectal adenocarcinoma-related mutations in goblet cell carcinoids and their ex-goblet cell carcinoid variants, we decided to take our sequencing approach one step further and investigated selected cases from both subgroups with a large-scale next-generation sequencing panel, which covers nearly all exons from 409 cancer-related genes. Interestingly, both goblet cell carcinoids and adenocarcinomas ex-goblet cell carcinoid harbored alterations in genes (USP9X, NOTCH1, CTNNA1, and CTNNB1, TRRAP, respectively), whose transcriptional products are known to be directly involved or interact with the Wnt-signaling pathway, [27][28][29][30][31][32] that is thought to have an important role in intestinal proliferation and differentiation. 35,36 It is therefore possible, that alterations of Wnt-signaling pathwayassociated proteins, beside APC, may be of significance for the development of appendiceal goblet cell carcinoids and their high-grade variants.…”
Section: Discussionmentioning
confidence: 99%
“…Worthy of note, three of the four goblet cell related neoplasms, that underwent additional large-scale sequencing, harbored mutations in genes (USP9X, NOTCH1, CTNNA1, CTNNB1, TRRAP), which are known to be directly involved or to interact with the Wnt-signaling pathway. [27][28][29][30][31][32]…”
Section: Additional Large-scale Sequencing Of Goblet Cell Carcinoidsmentioning
confidence: 99%
“…Interestingly, USP9X regulates pathways with known or potential roles in SSCs by deubiquitylating and stabilising protein components, e.g. Wnt/βcatenin, Notch and Hippo (Premarathne et al, 2017;Toloczko et al, 2017;Yang et al, 2016). USP9X binds and inhibits mTORC1 in muscle progenitors (Agrawal et al, 2012), suggesting that GILZdependent mTORC1 inhibition is mediated in part through USP9X (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…4E,G). USP9X is a deubiquitylase that regulates cellular pathways by modulating protein stability (Bridges et al, 2017;Premarathne et al, 2017). Germline Usp9x deletion blocks spermatogenesis and is associated with spermatocyte apoptosis (Kishi et al, 2017).…”
Section: Identification Of Gilz Effector Genes In Spermatogoniamentioning
confidence: 99%
“…USP4 can positively regulate the Wnt signaling in colorectal cancer [86]. Previous studies indicated that USP9X increases adhesion by destabilizing β-catenin [87]. USP14 and USP34 are required for Wnt signaling, but the detailed molecular mechanism is not yet known [88].…”
Section: Usps Regulate Related Pathways To Control Cancer Metastasismentioning
confidence: 99%